Associations Between Physician Supply Levels and Amenable Mortality Rates: An Analysis of Taiwan Over Nearly 4 Decades. (September 2020) - Chen, Brian K; Jindal, Dakshu; Yang, Y. Tony; Hair, Nicole; Yang, Chun-Yuh
Access to health care is an important determinant of health, but it remains unclear whether having more physicians reduces mortality. In this study, we used Taiwan's population-level National Death Certification Registry data to investigate whether a greater supply of physicians is associated with lower rates of amenable mortality, defined as deaths that can be delayed with appropriate and timely medical treatment. Our baseline regression analysis adjusting only for age and sex shows that an increase in the number of physicians per 1000 is associated with a reduction of 1.7 ( P < .01) and 0.97 ( P < .01) age-standardized deaths per 100 000 for men and women, respectively. However, in our full analyses that control for socioeconomic factors and Taiwan's health insurance expansion, we find that physician supply is no longer statistically associated with amenable mortality rates. Nevertheless, we found that greater physician supply levels are associated with a reduction in deaths from ischemic heart disease (−0.13 ( P < .05) for men, and −0.066 ( P < .05) for women). These findings suggest that overall, physician supply is not associated with amenable mortality rates after controlling for socioeconomic factors but may help reduce amenable mortality rates in specific causes of death.